Changes in the NK Cell Repertoire Related to Initiation of TB Treatment and Onset of Immune Reconstitution Inflammatory Syndrome in TB/HIV Co-infected Patients in Rio de Janeiro, Brazil—ANRS 12274 - Giacoia-Gripp, Carmem Beatriz Wagner; Cazote, Andressa da Silva; da Silva, Tatiana Pereira; Sant'Anna, Flávia Marinho; Schmaltz, Carolina Arana Stanis; Brum, Tania de Souza; de Matos, Juliana Arruda; Silva, Júlio; Benjamin, Aline; Pilotto, José Henrique; Rolla, Valeria Cavalcanti; Morgado, Mariza Gonçalves; et al. (Frontiers in Immunology, 2019)
Tuberculosis (TB) is the most common comorbidity and the leading cause of death among HIV-infected individuals. Although the combined antiretroviral therapy (cART) during TB treatment improves the survival of TB/HIV patients, the occurrence of immune reconstitution inflammatory syndrome (IRIS) in some patients poses clinical and scientific challenges. This work aimed to evaluate blood innate lymphocytes during therapeutic intervention for both diseases and their implications for the onset of IRIS. Natural killer (NK) cells, invariant NKT cells (iNKT), γδ T cell subsets, and in vitro NK functional activity were characterized by multiparametric flow cytometry in the following groups: 33 TB/HIV patients (four with paradoxical IRIS), 27 TB and 25 HIV mono-infected subjects (prior to initiation of TB treatment and/or cART and during clinical follow-up to 24 weeks), and 25 healthy controls (HC). Concerning the NK cell repertoire, several activation and inhibitory receptors were skewed in the TB/HIV patients compared to those in the other groups, especially the HCs. Significantly higher expression of CD158a (p = 0.025), NKp80 (p = 0.033), and NKG2C (p = 0.0076) receptors was detected in the TB/HIV IRIS patients than in the non-IRIS patients. Although more NK degranulation was observed in the TB/HIV patients than in the other groups, the therapeutic intervention did not alter the frequency during follow-up (weeks 2–24). A higher frequency of the γδ T cell population was observed in the TB/HIV patients with inversion of the Vδ2+/Vδ2− ratio, especially for those presenting pulmonary TB, suggesting an expansion of particular γδ T subsets during TB/HIV co-infection. In conclusion, HIV infection impacts the frequency of circulating NK cells and γδ T cell subsets in TB/HIV patients. Important modifications of the NK cell repertoire were observed after anti-TB treatment (week 2) but not during the cART/TB follow-up (weeks 6–24). An increase of CD161+ NK cells was related to an unfavorable outcome. Despite the low number of cases, a more preserved NK cell profile was detected in IRIS patients previous to treatment, suggesting a role for these cells in IRIS onset. Longitudinal evaluation of the NK repertoire showed the impact of TB treatment and implicated these cells in TB pathogenesis in TB/HIV co-infected patients.